Extracellular Adenosine Triphosphate (eATP) and Its Metabolite, Extracellular Adenosine (eAdo), as Opposing “Yin–Yang” Regulators of Nlrp3 Inflammasome in the Trafficking of Hematopoietic Stem/Progenitor Cells - Ratajczak, Mariusz Z.; Kucia, Magda (Frontiers in Immunology, 2021)
Nlrp3 inflammasome plays a pleiotropic role in hematopoietic cells. On the one hand, physiological activation of this intracellular protein complex is crucial to maintaining normal hematopoiesis and the trafficking of hematopoietic stem progenitor cells (HSPCs). On the other hand, its hyperactivation may lead to cell death by pyroptosis, and prolonged activity is associated with sterile inflammation of the BM and, as a consequence, with the origination of myelodysplasia and leukemia. Thus, we need to better understand the actions of this protein complex in order to define the boundaries of its safety window and to study the transition of from being beneficial to being detrimental. We have demonstrated that Nlrp3 inflammasome is expressed and active both in HSPCs and in the non-hematopoietic cells that are constituents of the bone marrow (BM) microenvironment. Importantly, Nlrp3 inflammasome responds to mediators of purinergic signaling, and while extracellular adenosine triphosphate (eATP) activates this protein complex, its metabolite extracellular adenosine (eAdo) has the opposite effect. In this review we will discuss the physiological consequences of the balance between eATP and eAdo in regulating the trafficking of HSPCs in an Nlrp3 inflammasome-dependent manner, as seen during pharmacological mobilization form BM into peripheral blood (PB) and in the reverse mechanism of homing from PB to BM and engraftment. We propose that both mediators of purinergic signaling and the Nlrp3 inflammasome itself may become important therapeutic targets in optimizing the trafficking of HSPCs in clinical settings.